Technology transfer, essence of the Linkage with Society. Case of La Concordia - Ecuador (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The objective of this research was to analyze the contribution of theactivities of the students who took the community service subjects in2021 to the strengthening of technology transfer in the La Concordiacanton of the Santo Domingo de Los Tsáchilas province and its areaof influence. Its contribution to the training processes and thereforeto the link with society is shown at the career level. The leading roleof directors, teachers and students of the university institution incollaborating in the development of the linking activities reflected inthe study of student intervention in the canton of La Concordia isrecognized. As a result of this documentary analysis, we have that 300students and 43 teachers participated, providing 49 training courses,between the academic periods 2020-2s and 2021-1s, in the midst ofthe Covid-19 pandemic.